2009
DOI: 10.1007/s10741-008-9124-8
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on the clinical application of troponin in heart failure and states of cardiac injury

Abstract: The ability to measure the appearance of cardiac specific forms of troponin in the blood represents a major advance in the clinical assessment of patients with many types of cardiovascular disease, especially acute coronary syndromes. In this review we focus on the utility of troponin in heart failure where this biomarker has emerged as an independent predictor of prognosis providing information beyond clinical assessment and measurement of b-type natriuretic peptides. The novel clinical role of troponin in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Cardiac tissue damage, like cell death or necrosis with myofilament injuries, will inevitably cause cTn elevation. Meanwhile, the severity of cardiac damage can be reflected by the level of increased cTn ( Bass et al, 2010 ). Mir and Heinzerling have reported that some cases with PD-1/PD-L1 inhibitor immunotherapy-related heart failure, cardiomyopathy, myocarditis, and myocardial fibrosis may manifest normal troponin levels ( Heinzerling et al, 2016 ; Mir et al, 2018 ).…”
Section: Diagnosismentioning
confidence: 99%
“…Cardiac tissue damage, like cell death or necrosis with myofilament injuries, will inevitably cause cTn elevation. Meanwhile, the severity of cardiac damage can be reflected by the level of increased cTn ( Bass et al, 2010 ). Mir and Heinzerling have reported that some cases with PD-1/PD-L1 inhibitor immunotherapy-related heart failure, cardiomyopathy, myocarditis, and myocardial fibrosis may manifest normal troponin levels ( Heinzerling et al, 2016 ; Mir et al, 2018 ).…”
Section: Diagnosismentioning
confidence: 99%
“…2 The use of biomarkers as a tool in outcome prediction for these patients is a relatively novel concept for which there is an expanding evidence base. Cardiac smooth muscle troponin (cTn) is well established as a sensitive and early indicator of cardiac injury 3 but further to this cardiac role, studies in critically ill patients have demonstrated an association between elevated cTn levels and increased morbidity, mortality and length of stay in both unselected medical and non-cardiac surgical patients. 47 It remains unclear whether the different cTn subunits, troponin I (cTnI), troponin T (cTnT) and C (cTnC), are of equivalent diagnostic and prognostic significance in the non-acute coronary syndrome setting.…”
Section: Introductionmentioning
confidence: 99%
“…Although the clear pathophysiological process is not well characterised, it more likely represents a spectrum of changes ranging from cell death and frank necrosis with myofilament disruption to less severe and likely transient changes in the integrity and permeability of the sarcolemma membrane. This implies that irrespective of the causative factors, cardiac injury will inevitably lead to an elevated plasma level of cTn, and the level of increase reflects the severity of damage [22].…”
Section: Evidence Supporting the Hypothesesmentioning
confidence: 99%